Helping the man in the middle: assessing and training referee performance - Mascarenhas, (Duncan Richard David (The University of Edinburgh, 2005)
This thesis describes an applied programme of research with the English Rugby Football Union (RFU) national panel of referees. Referee performance can have a critical impact on the outcomes of games and as a consequence the future status of the clubs & players concerned. Surprisingly, given the importance of referees, access to scientific support for these individuals is almost non-existent. Furthermore, there are only a handful of empirical investigations that have explored refereeing performance and none that has attempted to train sports officials. Accordingly, this programme of research set out to understand, operationalise and train the key aspects of referee performance. Using a multi-modal approach the first investigation used referee performance profiling and content analyses of three sources of literature to establish the key areas of referee performance. The Cornerstones Performance Model of Refereeing emerged, overarched by the psychological characteristics of excellence; featuring knowledge and application of the law; contextual judgment; personality and management skills; and fitness and positioning. The model was subsequently adopted by the RFU to structure the applied support programme and guide the development and selection of the English RFU referees. A naturalistic approach was adopted, focussing primarily on the decision-making aspects of the performance model. A video based, law-application assessment tool revealed surprisingly low levels of accuracy amongst referees and their support groups. Accordingly, a training programme was designed to reinforce accurate and coherent interpretations. A group of national panel referees watched videotaped scenarios taken from premier league games, showing 5 sets of 5 tackles, in each case with an expert providing the interpretation of the correct decision. All referee groups improved their performance from pre to posttest, with the lowest ranked referees showing significant improvements. However, as the performance model presents, referee DM is influenced by many factors beyond a simple application of the law. Accordingly, the final investigation explored the factors that change the game context and how they influence rugby-union referees management of the game. Following the nominal group technique, two groups of referees listed contextual factors that they felt might affect their decisions during a game. Individual ratings of this list with both groups revealed the most important factors to be the "temper of the game," "the level of player respect/rapport," "position on pitch," "scoreline," and the "time left in the game." To verify these factors a think-aloud protocol was conducted with three international referees, assessing how they weigh their decisions based on the context and how this affects their management of the game. The results suggest that elite referees use "preventative refereeing" to help maintain the natural flow to a game. Finally, the implications of this research programme are discussed in the light of expediting the development of high performance referees in open team sports.